Relationship of Education Level on The Success of Tuberculosis Treatment in Kupang City - Dedy, Maria Agnes Etty; Sagita, Sidarta; Artawan, I Made; Inaya, Farah (Faculty of Public Health, Nusa Cendana University, 2023)
The low success rate of pulmonary TB treatment from 2016 to 2017 which decreased from 87.79% to 84.05% and Kupang City itself in 2017 had a treatment success rate of 78.72% which is still far below the national achievement target. Many factors influence the success of pulmonary TB treatment in Kupang City, including the level of education, occupation and the role of the PMO. The purpose of this study was to determine (1) the description of the education level of pulmonary TB patients in Kupang City, and (2) the relationship between education level and the success of treatment of pulmonary TB patients in Kupang City. The method used in this research is an analytical survey with a cross sectional design. The population in this study amounted to 378 cases with a sample of 79 samples with the stratify random sampling method. The results showed that there was no relationship between low and high education on the success of tuberculosis treatment in Kupang City with a p-value of 1,000 (Chi-square test (p>0.05), Contingency Coeficient 0.034. Chi-Square test results did not meet the requirements because there are cells with an expected frequency of < 5 and > 20% of all cells, then proceed with the Fisher's Exast test to get the Asymp.Sig (2-Sided) value or p-value of 1,000, because the p-value (0.000) Alpha ( 0.05) it can be concluded that there is no relationship between the level of education and the success of treatment of pulmonary TB patients in Kupang City. From the Contingency Coeficient value obtained a value of 0.034 which means that the close relationship is unidirectional and the close relationship is weak. The conclusions obtained are (1) mostly respondents with low education level managed to recover and a small proportion of respondents with low education were successful in the treatment of pulmonary TB in Kupang City, (2) There is no relationship between education level n and the success of tuberculosis treatment in Kupang City.